Predictors of long-term survival in patients undergoing residential cardiac rehabilitation (rCR) after transcatheter aortic valve replacement (TAVR): a multicenter retrospective study. (14th October 2021) - Tarro Genta, F; Marcassa, C; Ceresa, M; Scalvini, S; Dalla Vecchia, L A; Bussotti, M; Iannuzzi, G L; Rizzo, C; Pedretti, R F E; Giordano, A; La Rovere, M T
Abstract: Purpose: To evaluate exercise-based rCR derived outcome predictors in patients referred after TAVR. Methods: Data of 232 patients (aged 82±6 years, 45%males) admitted to an average 3-week rCR program after TAVR (walking, up to 30 minutes of cycling or treadmill session twice daily, respiratory and calisthenic training) from January 2009 to December 2017 and home discharged, were retrospectively collected at 10 rCR Divisions of Istituti Clinici Scientifici Maugeri. Comorbidity (cumulative illness rated state-comorbidity index) (CIRS-CI) score, echocardiography on admission, disability (Barthel Index) (BI) score at discharge, six minutes walking test distance (6MWT) on discharge and maximal training session intensity (MTSI expressed in METs per minutes) were collected. All-cause mortality was assessed up to 3 years after rCR discharge. Results: During a 3-year follow-up, there were 74 (32%) deaths. At univariate analysis, at discharge non survivors compared to survivors had significantly higher comorbidity rate (CIRS-ICC 5.2±2.3 vs 4.1±1.9, p=0.000) and disability level (BI 80.4±24 vs 88.8±17, p=0.000). Moreover, they had worse renal function (creatinine 1.6±0.9mg/dl vs 1.2±0.4, p=0.000), were more often on diuretic therapy (73% vs 53.2%, p=0.003) and on beta-blocker therapy (73% vs 57, 6%, p=0.042) and had a markedly reduced functional capacity (6MWTD 221±100m vs 265±105m, p=0.001). At multivariate logistic stepwise analysis a lower comorbidity (CIRS-ICC), a more preserved renal function (creatinine level), a reduced use of diuretic therapy and 6MWT at discharge confirmed their power as independent predictors of survival at follow up (Table, Harrel's C = 0.707) Conclusions: Patients attending rCR after TAVR are very old with significant comorbidity; overall mortality at 3-year follow-up after CR discharge is substantial. Our results suggest the need to implement ad-hoc long-term care strategies based on residual exercise capacity, comorbidity score and renal function for tailoring follow-up in patients discharged from rCR after TAVR. Funding Acknowledgement: Type of funding sources: None.